The health risks of Columba livia Infestation: A public Health Concern of Thane District, Maharashtra - Salunke, Sanjay B.; Shaikh, Shahjahan A. (International Journal of Scientific Research in Biological Sciences, 2025)
Columba livia, commonly known as the domestic pigeon, is a ubiquitous bird species found throughout the country. With a long history of association with humans, pigeons have been domesticated for various purposes, including food, sports, research, and as ornamental birds. However, the close association between pigeons and humans has a darker side. As pigeons come into contact with human populations, they pose a significant risk to public health. These birds can carry a variety of pathogens, including bacteria, viruses, and fungi, which can cause diseases in humans. The proximity of pigeons to human settlements, coupled with their ability to thrive in urban environments, makes them a potential reservoir for zoonotic diseases. The present study deals with the health issues when get exposed to pigeon.